Investigating relationship between managerial capabilities and entrepreneurial orientation with medium-sized cooperatives performance in Malaysia - Abd Aziz, Mohd Faiq; Mahadi, Nomahaza; Azizul, Muhd. Dhamir Audi; Nordin, Nur Anis (Zhongguo Hangtian Gongye Zonggongsi, 2024)
A cooperative is a business that strives to benefit and support its members through revenue-generating endeavors. Management's capacity to reorganize and combine organizational resources and competences is known as managerial capabilities. The managerial members of medium-sized cooperatives in Malaysia are considered to have managerial competencies for the purposes of this study. The proactive and creative mentality displayed by medium-sized cooperatives in Malaysia is referred regarded as an entrepreneurial orientation. In the quest of improved performance, it includes the cooperative's readiness and capacity to recognize and seize new possibilities, investigate cutting-edge strategies, and take measured risks. However, a study on the association between managerial capabilities and entrepreneurial orientation with medium-sized cooperatives performance in Malaysia still scarce. A total of 250 questionnaires were disseminated using email among cooperatives in Malaysia in order to collect the data; however, only 138 usable responses were gathered and employed for data analysis. Statistical Package for Social Science (SPSS) version 23 and SmartPLS version 3.3.8 were then used to analyze the data in this study using a combination of descriptive and inferential statistics. The results indicate a positive relationship between management capabilities and cooperative performance. Based on the findings the relation between managerial capabilities and cooperative performance is significant. However, there is no significant correlation between the entrepreneurial orientation construct and cooperative performance. As a conclusion, the study's outcomes hold the potential to directly impact the cooperative sector's trajectory in Malaysia. By addressing entrepreneurial orientation and management capabilities, this research stands to enhance the performance of Malaysian cooperatives.